(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Objective The main objective of our study is to Prevent heart and blood vessels disease retrospective adherence of quadruple therapy for coronary artery disease in a teritary care corporate hospital Method Quadruple therapy of coronary artery disease data of 150 cardiac patients, attending medicine. In and out patients of Sunshine Corporate hospital from June 2018 to February 2019 was collected from hospital. Results 150 patients were enrolled in this study A total number of 150 patients were taken Aspirin were 60 (40%), Clopidogrel were 13 (8.7%), Ticagrelor were 7 (4.7%), Prasugrel were 13 (8.7%), Heparin were 15 (10%), Bivacardin were 3 (2%), LMWH were 5 (3.3%), Atropin were 12 (8%), Adrenaline were 2 (1.3%), Norepinephrine were 5 (3.3%), Sodium Bicarbonate were 5 (3.3%). The prescription pattern was found to be accordance with WHO guidelines. Conclusion In according with the WHO guidelines and medicine adherence is very low in people and we should make the patients aware of coronary artery disease by conducting patient education programs and by conducting some awareness programs.